2011
DOI: 10.3109/09637486.2011.584860
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed electric field on the rheological and colour properties of soy milk

Abstract: The effects of pulsed electric field (PEF) treatments on rheological and colour properties of soy milk were evaluated. Flow behaviour, viscosity and rheological parameters of PEF-treated soy milk were monitored using a controlled stress rheometer. For PEF treatments, electric field intensity of 18, 20 and 22 kV cm(-1) and number of pulses of 25, 50, 75 and 100 were used. For the measurements of rheological properties of soy milk shear rates between 0 and 200 s(-1) was used. The rheological behaviour of control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…During all treatments, the apparent viscosity of the spinach juice was significantly ( P < 0.05) reduced with the increase of shear rate from 0 to 100 s −1 and led to a rapid breakdown of initial shearing. This response during PEF might be attributed to the combined effects of breakdown and reformation of weak linkage between proteins and molecular collisions and Brownian motion (Xiang, Simpson, Ngadi, & Simpson, 2011). The juice sample treated with US‐PEF in the present study indicated similar results already reported by Medina‐Meza et al.…”
Section: Resultsmentioning
confidence: 99%
“…During all treatments, the apparent viscosity of the spinach juice was significantly ( P < 0.05) reduced with the increase of shear rate from 0 to 100 s −1 and led to a rapid breakdown of initial shearing. This response during PEF might be attributed to the combined effects of breakdown and reformation of weak linkage between proteins and molecular collisions and Brownian motion (Xiang, Simpson, Ngadi, & Simpson, 2011). The juice sample treated with US‐PEF in the present study indicated similar results already reported by Medina‐Meza et al.…”
Section: Resultsmentioning
confidence: 99%
“…A decrease in free sulfhydryl groups is generally attributable to the formation of disulphide bridges at both intra-and intermolecular structural level. Covalent cross-linking would favour transient selfassembly of proteins, potentially leading to the formation of aggregates with modified surface activity and functional properties (Li et al 2007;Liu et al 2011;Wu et al 2016;Xiang et al 2011b). In gluten suspension at pH 6, the decrease of sulfhydryl groups was clearer as compared to the one observed in pea samples (Table 1).…”
Section: Effect Of Mipef Treatment On Protein Structurementioning
confidence: 94%
“…These events can lead finally to a decrease in the ordered structures (α-helices), an increase in disorder ones (β-sheets, β-turns and random coils) and a higher exposure of surface free sulfhydryls (S-H) (Guan et al 2010;Liu et al 2013). As summarized by Giteru et al (2020), all these modifications generate the formation of transient structures and changes in the interfacial properties of the proteins, which influence their functional properties including surface hydrophobicity (Li et al 2007;Wu et al 2016), colloidal behaviour (Xiang et al 2011b), thermal stability (Liu et al 2011) and swelling index (Li et al 2007). To this regard, it is noteworthy that structural modification of enzymes, such as papain, POD, PPO, lysozyme and LOX, exposed to PEF was found to be responsible for their irreversible inactivation (Luo et al 2010;Yeom et al 1999;Yang 2008, 2010;Zhong et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This structure transition resulted from the interaction between the ricin’s secondary structures and the nsPEFs. It was previously reported that polypeptide chains of protein could be affected by an external electric field 56 57 . Zhao et al revealed that the nsPEFs could trigger an augment in the dielectric constant of protein, thus inducing the unfolding of polypeptide, and then the secondary and tertiary structures of protein would vary 58 .…”
Section: Resultsmentioning
confidence: 99%